Based on CRISPR-Cas13a system, to establish a rapid visual detection method for avian influenza viruses - Zhang, Zongshu; Wang, Chunguang; Chen, Xi; Zhang, Zichuang; Shi, Guoqiang; Zhai, Xianghe; Zhang, Tie (Frontiers in Veterinary Science, 2024)
To rapidly, specifically, and sensitively detect avian influenza virus (AIV), this research established a visual detection method of recombinase-aided amplification (RAA) based on Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and CRISPR associated proteins 13a (Cas13a) system. In this study, specific primers and CRISPR RNA (crRNA) were designed according to the conservative sequence of AIV Nucleprotein (NP) gene. RAA technology was used to amplify the target sequence, and the amplification products were visually detected by lateral flow dipstick (LFD). The specificity, sensitivity, and reproducibility of RAA-CRISPR-Cas13a-LFD were evaluated. At the same time, this method and polymerase chain reaction (PCR)-agarose electrophoresis method were used to detect clinical samples, and the coincidence rate of the two detection methods was calculated. The results showed that the RAA-CRISPR-Cas13a-LFD method could achieve specific amplification of the target gene fragments, and the detection results could be visually observed through the LFD. Meanwhile, there was no cross-reaction with infectious bronchitis virus (IBV), infectious laryngotracheitis virus (ILTV), and Newcastle disease virus (NDV). The sensitivity reached 100 copies/μl, which was 1000-fold higher than that of PCR-agarose electrophoresis method. The coincidence rate of clinical tests was 98.75 %, and the total reaction time was approximately 1 hour. The RAA-CRISPR-Cas13a-LFD method established in this study had the advantages of rapid, simple, strong specificity, and high sensitivity, which provided a new visual method for AIV detection.